EVALUATION OF CONSTRAINTS FACED BY FARMERS IN ADOPTION OF DAIRY CATTLE MANAGEMENTAL PRACTICES - Shisode, M G; Dhumal, M V; Siddiqui, M F; Kulkarni, M D; Ulemale, A H; Khanvilkar, A V; Siddiqui, M B A; Samant , S R; Komatwar , S J (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
The constraints expressed by the dairy cattle owners of Rajarambapu Patil Sahakari Dudh Sangh Ltd. Islampur as regards the reproduction, nutrition, management, health, economic and milk distribution were studied. Some remedial measures like trainings, exhibitions, brain storming sessions, poster presentations, radio talks and programmes on Door-darshan can be taken up to create awareness in dairy farmers and to impart knowledge to them to undertake new animal managemental practices to increase the milk yield.